Projected Changes in Precipitation Extremes Over Jiulongjiang River Basin in Coastal Southeast China - Li, Chang; Dike, Victor Nnamdi; Lin, Zhaohui; Gao, Xuejie (Frontiers in Earth Science, 2021)
The southeast coastal region of China is susceptible to challenges related to extreme precipitation events, hence projection of future climate extremes changes is crucial for sustainable development in the region. Using the Regional Climate Model Version 4 (RegCM4), the future changes of summer precipitation extremes have been investigated over the Jiulongjiang River Basin (JRB), a coastal watershed in Southeast China. Comparison between the RegCM4 simulated and observed rainy season precipitation over JRB suggests that the RegCM4 can reasonably reproduce the seasonal precipitation cycle, the frequency distribution of precipitation intensity, and the 50-yr return levels of precipitation extremes over JRB. Furthermore, the model projects an increase in daily maximum rainfall (RX1day) mostly over the northern part of the basin, and a decrease over other parts of the basin, while projecting a widespread decrease for maximum consecutive 5-day precipitation amount (RX5day) relative to the present day. In terms of 50-year return level of RX1day (RL50yr_RX1day), a general increase is projected over most parts of the basin in the near and far future of the 21st century, but a decrease can be found in the northeast and southwest part of the JRB in the mid-21st century. The future change of 50-yr return level of RX5day (RL50yr_RX5day) shows a similar spatial pattern with that of RL50yr_RX1day in the near and mid-21st century, but with a larger magnitude. However, a remarkable decrease in RL50yr_RX5day is found in the south basin in the far future. Meanwhile, the projected changes in 50-yr return level for both RX1day and RX5day differ between the first and second rainy season in JRB. Specifically, the future increase in RL50yr_RX5day over the north basin is mainly contributed by the changes during the first-half rainy season, while the decrease of RL50yr_RX5day in the south is mostly ascribed to the future changes during the second-half rainy season. All above results indicate that the future changes of rainfall extremes in JRB are much complicated, which might differ from extremes indices, seasons, as well as future projected periods. And these will thus be of practical significance for flood risk management, mitigation, and adaptation measures in JRB.